Petrogenesis of the Early Eocene adakitic rocks in the Napuri area, southern Lhasa: Partial melting of thickened lower crust during slab break-off and implications for crustal thickening in southern Tibet - Ma, L.; Wang, B.; Jiang, Z.; Wang, Qiang; Li, Zheng-Xiang; Wyman, D.; Zhao, S.; Yang, J.; Gou, G.; Guo, H. (Elsevier BV, 2014)
Cenozoic adakitic rocks in the Lhasa block (southern Tibet) have been widely used to trace the lateral extent of crustal thickening. However, their petrogenesis remains controversial. Here, we report geochronological and geochemical data for the Napuri intrusive rocks in the core area of the Quxu batholith, southern Lhasa. Zircon U–Pb dating suggests that they were generated at approximately 48 Ma. The studied samples show significant geochemical variations, manifested by the coexistence of three types of igneous rocks. Groups I and II rocks exhibit variable and high SiO2 (66.4–73.9 wt.%), high Al2O3 (14.0–17.4 wt.%), K2O (3.9–5.3 wt.%), Sr (273–718 ppm) and Sr/Y (18.3 to 81.3) values, and low Y (3.6 to 16 ppm), heavy rare earth element (REE) (e.g., Yb = 0.48 to 1.8 ppm), MgO (0.4–1.0 wt.%), Cr (2.9–7.4 ppm) and Ni (1.6–4.5 ppm) contents, which are similar to those of thickened lower crust-derived adakitic rocks. The Group I rocks show higher Sr/Y (77.5–81.3) ratios and lower total REE (55.5–63.2 ppm) contents with clearly positive Eu and Sr anomalies, whereas the Group II rocks have relatively lower Sr/Y (18.3–65.7) ratios and higher total REE (115–375 ppm) contents with negligible or slightly negative Eu and Sr anomalies. Group III rocks have the highest SiO2 (74.5–76.0 wt.%), Y (17.0–23.7 ppm) and Yb (2.91–3.30 ppm) contents, and the lowest Al2O3 (12.5–13.2 wt.%), Sr (81.3–141 ppm) and Sr/Y (4.8–5.9) values with distinctly negative Eu and Sr anomalies. Compared with the Jurassic–Cretaceous granitoids in southern Lhasa, the relative enrichment in Sr–Nd–Hf isotopic compositions ((87Sr/86Sr)i = 0.7049–0.7055, εNd(t) = − 0.3 ± 0.7 and εHf(t)zircon = + 3.6 ± 11.4) for the Napuri intrusive rocks indicates that they likely contained Indian continental components. The Group I and Group II rocks most probably originated from thickened mafic lower crust (amphibolite eclogites or garnet amphibolites) with garnet + rutile ± plagioclase as residual minerals in the source at > 1.5 GPa, corresponding to depths of > 50 km, and Group III rocks were probably generated by fractional crystallization of plagioclase from the adakitic magmas. Taking into account the narrow linear nature of the Eocene magmatic belt and reported synchronous asthenosphere-derived basaltic rocks in southern Lhasa, we suggest that upwelling asthenosphere triggered by the break-off of subducted Neo-Tethyan slab probably provided the required thermal conditions for lower crustal melting. The identification of Indian continental components in the Napuri intrusive rocks probably indicates that the Asia–India collision had taken place prior to their emplacement. The dramatic changes in the (La/Yb)N ratios and εNd(t) and εHf(t) values of magmatic rocks in the Gangdese area at ca. 51–46 Ma indicate that the Cenozoic crustal thickening associated with the indentation of the Indian continent began in the Early Eocene (ca. 51–46 Ma) at the latest.